2022
DOI: 10.1038/s41467-022-30482-6
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional seroprevalence surveys of SARS-CoV-2 antibodies in children in Germany, June 2020 to May 2021

Abstract: The rate of SARS-CoV-2 infections in children remains unclear due to many asymptomatic cases. We present a study of cross-sectional seroprevalence surveys of anti-SARS-CoV-2 IgG in 10,358 children recruited in paediatric hospitals across Germany from June 2020 to May 2021. Seropositivity increased from 2.0% (95% CI 1.6, 2.5) to 10.8% (95% CI 8.7, 12.9) in March 2021 with little change up to May 2021. Rates increased by migrant background (2.8%, 4.4% and 7.8% for no, one and two parents born outside Germany). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 28 publications
3
20
1
6
Order By: Relevance
“…The proportion of children with positive titers against SARS-CoV-2 immunoglobulin G (IgG) was recently published for the SARS-CoV-2 KIDS study [ 8 ]. This is a hospital-based, multi-center, longitudinal study in children aged ≤ 17 years.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportion of children with positive titers against SARS-CoV-2 immunoglobulin G (IgG) was recently published for the SARS-CoV-2 KIDS study [ 8 ]. This is a hospital-based, multi-center, longitudinal study in children aged ≤ 17 years.…”
Section: Methodsmentioning
confidence: 99%
“…The SARS-CoV-2 KIDS study authors reported a seroprevalence of SARS-CoV-2 IgG antibodies of 10.8% (95% CI 8.7, 12.9) for March 2021, and observed no major change through May 2021 [ 8 ]. Additionally, by the end of the observation period, they detected no differences in seroprevalence among the different age groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strength of our analysis is the use of population-based data and the inclusion of more than 5 million con rmed infections with a uniform, widely available testing strategy during the observation periodwith more than 30% of seropositive cases identi ed as of March 2021 [19].…”
Section: Discussionmentioning
confidence: 99%